Polyoxomolybdenum(V/VI)-sulfite compounds: synthesis, structural, and physical studies - Kapakoglou, Nikolaos I.; Betzios, Panagiotis I.; Drouza, Chryssoula (My University, 2007)
Reaction of Na 2Mo VIO 4·2H 2O with (NH 4) 2SO 3 in the mixed-solvent system H 2O/CH 3CN (pH = 5) resulted in the formation of the tetranuclear cluster (NH 4) 4[Mo 4 VISO 16]·H 2O (1), while the same reaction in acidic aqueous solution (pH = 5) yielded (NH 4) 4[Mo 5 VIS 2O 21] ·3H 2O (2). Compound {(H 2bipy) 2[Mo 5 VIS 2O 21]·H 2O} x (3) was obtained from the reaction of aqueous acidic solution of Na 2Mo VIO 4·2H 2O with (NH 4) 2SO 3 (pH = 2.5) and 4,4′-bipyridine (4,4′-bipy). The mixed metal/sulfite species (NH 4) 7[Co III(Mo 2 VO 4)(NH 3)(SO 3) 6]·4H 2O (4) was synthesized by reacting Na 2Mo VIO 4·2H 2O with CoCl 2· 6H 2O and (NH 4) 2SO 3 with precise control of pH (5.3) through a redox reaction. The X-ray crystal structures of compounds 1, 2, and 4 were determined. The structure of compound 1 consists of a ring of four alternately face- and edge-sharing Mo VIO 6 octahedra capped by the trigonal pyramidal sulfite anion, while at the base of the Mo 4 ring is an oxo group which is asymmetrically shared by all four molybdenum atoms. Compound 3 is based on the Strandberg-type heteropolyion [Mo 5 VIS 2O 21] 4-, and these coordinatively saturated clusters are joined by diprotonated 4,4′-H 2bipy 2+ through strong hydrogen bonds. Compound 3 crystallizes in the chiral space group C2. The structure of compound 4 consists of a novel trinuclear [Co IIIMo 2 VSO 3 2-] cluster. The chiral compound 3 exhibits nonlinear optical (NLO) and photoluminescence properties. The assignment of the sulfite bands in the IR spectrum of 4 has been carried out by density functional calculations. The cobalt in 4 is a d 6 octahedral low-spin metal atom as it was evidenced by magnetic susceptibility measurements, cw EPR, BVS, and DFT calculations. The IR and solid-state UV-vis spectra as well as the thermogravimetric analyses of compounds 1-4 are also reported
Keywords: Bipyridinium compounds; X-ray crystallography; Molybdenum compounds; Hydrogen bonding; Photoluminescence; Thermogravimetry